Frontline Science: The expression of integrin αDβ2 (CD11d/CD18) on neutrophils orchestrates the defense mechanism against endotoxemia and sepsis. Issue 5 (13th January 2021) - Bailey, William P; Cui, Kui; Ardell, Christopher L; Keever, Kasey R; Singh, Sanjay; Rodriguez-Gil, Diego J; Ozment, Tammy R; Williams, David L; Yakubenko, Valentin P
Abstract: Neutrophil-macrophage interplay is a fine-tuning mechanism that regulates the innate immune response during infection and inflammation. Cell surface receptors play an essential role in neutrophil and macrophage functions. The same receptor can provide different outcomes within diverse leukocyte subsets in different inflammatory conditions. Understanding the variety of responses mediated by one receptor is critical for the development of anti-inflammatory treatments. In this study, we evaluated the role of a leukocyte adhesive receptor, integrin αD β2, in the development of acute inflammation. αD β2 is mostly expressed on macrophages and contributes to the development of chronic inflammation. In contrast, we found that αD -knockout dramatically increases mortality in the cecal ligation and puncture sepsis model and LPS-induced endotoxemia. This pathologic outcome of αD -deficient mice is associated with a reduced number of monocyte-derived macrophages and an increased number of neutrophils in their lungs. However, the tracking of adoptively transferred fluorescently labeled wild-type (WT) and αD −/− monocytes in WT mice during endotoxemia demonstrated only a moderate difference between the recruitment of these two subsets. Moreover, the rescue experiment, using i.v. injection of WT monocytes to αD -deficient mice followed by LPS challenge, showed only slightly reduced mortality. Surprisingly, the injection of WT neutrophils to the bloodstream of αD −/− mice markedly increased migration of monocyte-derived macrophage to lungs and dramatically improves survival. αD -deficient neutrophils demonstrate increased necrosis/pyroptosis. αD β2 -mediated macrophage accumulation in the lungs promotes efferocytosis that reduced mortality. Hence, integrin αD β2 implements a complex defense mechanism during endotoxemia, which is mediated by macrophages via a neutrophil-dependent pathway. Graphical Abstract: Expression of integrin αD β2 on neutrophils promotes macrophage migration to the lung and prevents the development of endotoxemia and sepsis.